The Prospect of Indonesian Islamic Banks after Merger | مستقبل البنوك الإسلامية الإندونيسية بعد صدور قانون الاندماج - Syarif Hidayatullah (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2021)
Bank is an institution that operates without interest, whose activities are to realize material benefits through the collection and distribution of funds in accordance with sharia, where aspects of the implementation of prudential principles and good governance are supervised by the OJK. While the system and mechanism for the fulfillment of sharia compliance, the institution that has an important role is the National Sharia Council (DSN) of the MUI to issue a fatwa on the conformity of sharia for a bank product. Then the POJK emphasized that all Islamic banking products should only be offered to the public after the bank received a fatwa from the DSN MUI and obtained permission from the OJK. In the operational order, each Islamic bank is also required to have a Sharia Supervisory Board (DPS) which functions for sharia supervision and as an advisor in answering questions regarding whether its activities are sharia-compliant or not.Islamic banking in Indonesia continues to develop gradually and progress. In recent years, Islamic Banking has been on the rise, triggered by the great desire of the public to obtain halalness in conflict with banks. This shows that the prospect of Bank Syariah Indonesia will improve, especially with the merger of three Islamic Banks in Indonesia, namely PT. Bank Mandiri Syariah, PT. BNI Syariah and PT. BRIS, Tbk. To become Bank Syariah Indonesia Tbk, which is expected by the government so that Indonesia can become a barometer of the Islamic economy in the world and will be ranked seventh in Indonesia based on assets.